ONTOLOGY, EPISTEMOLOGY, AXIOLOGY COUNSELING AND THE ROLE OF PSYCHOLOGY IN COUNSELING - Edil Rohisfi; Prayitno; Yeni Karneli (Literasi Nusantara, 2021)
This article discusses the ontology, epistemology, and axiology of counseling as well as the role of psychology in counseling by using references from relevant literature reviews. Counseling is a professional assistance service to a person or group of individuals for the effective handling and handling of everyday life that is not disturbed by an independent personal focus who is able to control themselves through the provision of various types of services and support activities in the learning process. Philosophical assumptions to build counseling as a science that can be assumed through ontology, epistemology, and counseling axiology. Counseling also plays a role and functions automatically in determining the behavior of the social sphere. As we know, psychology is the study of the symptoms of the human psyche. Psychological study is a study of individual behavior where guidance and counseling means providing an understanding of the targeted individual's behavior, therefore the role of psychology in counseling is very necessary and of course useful for the development of students later.